Evaluation of Serum Testosterone Level in Middle Aged Men with or without Metabolic Syndrome (Bangladesh Journal of Medical Biochemistry, 2025)
The worldwide prevalence of metabolic syndrome has increased dramatically over the past 20 years. In Bangladesh the incidence rate of metabolic syndrome is also increasing. Low testosterone has been shown to have an effect to develop obesity and metabolic syndrome in men, as evidenced by many studies. This cross-sectional analytical study carried out at Sir Salimullah Medical College & Mitford Hospital (SSMC&MH), Dhaka, Bangladesh from July 2020 to June 2021 aimed to evaluate serum testosterone levels in middle aged men with or without metabolic syndrome. A total of 70 subjects were included in this study with the age range from 30-59 years. Subjects were divided into two groups. Group A included middle aged men without metabolic syndrome and Group B included middle aged men with metabolic syndrome. Samples were taken by non-probability purposive sampling. Important variables in this study were age, height, weight, BMI and serum testosterone. Then serum testosterone levels were compared between the two groups. There was no significant association of metabolic syndrome with age in this study. BMI and waist circumference were significantly higher in Group B than that of Group A. The mean total testosterone level was significantly lower in subjects with metabolic syndrome.Bangladesh J Med Biochem 2021; 14(2): 59-64